FEATURES OF THE FORMATION OF THE TOURIST SERVICES REGIONAL MARKET - M. V. Frolova (Russian Journal of Economics and Law)
The article considers the features of functioning of market of tourist services that is limited by a region. Regional tourist market is shown as a combination of three relatively independent segments - inbound, outbound and local (intra-regional). Here is identifies the basic factors of development of each segment of the regional market of tourist services.